2010
DOI: 10.1111/j.1469-7580.2010.01309.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of VGF peptides in the human cortex and their selective changes in Parkinson’s and Alzheimer’s diseases

Abstract: VGF mRNA and its precursor-derived products are selectively expressed in certain neurons and promptly respond to neurotrophins and to neural ⁄ electrical activity. Proteomic studies have previously revealed a reduction in some VGF peptides in the cerebrospinal fluid of patients affected by Alzheimer's disease and other conditions, suggesting their potential diagnostic and clinical significance. As the presence of VGF peptides within the human cortex has been somewhat elucidated, they were studied postmortem in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 38 publications
6
77
0
Order By: Relevance
“…Determining the mechanisms that account for preferential differences in treatment response will enable future treatment strategies to exploit alternative pathways and molecular players in subsets of patients who do not respond to conventional medications. Moreover, since VGF has diverse roles in the hippocampus, including learning and memory [1,45,46], and is associated with impaired memory and Alzheimer’s Disease [11,12,66,67], it will also be important in future studies to explore the role of the VGF SNPs in neurodegenerative diseases as has been done for Val66Met BDNF polymorphism [68,69]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Determining the mechanisms that account for preferential differences in treatment response will enable future treatment strategies to exploit alternative pathways and molecular players in subsets of patients who do not respond to conventional medications. Moreover, since VGF has diverse roles in the hippocampus, including learning and memory [1,45,46], and is associated with impaired memory and Alzheimer’s Disease [11,12,66,67], it will also be important in future studies to explore the role of the VGF SNPs in neurodegenerative diseases as has been done for Val66Met BDNF polymorphism [68,69]. …”
Section: Discussionmentioning
confidence: 99%
“…VGF (non-acronymic) is a neuropeptide whose expression is upregulated by neurotrophins including brain-derived neurotrophic factor (BDNF) in the hippocampus [1]. VGF and its peptide products [2] have largely been studied for their role in metabolic homeostasis [3,4,5,6,7], pain [8,9,10], neurodegeneration [11,12,13,14] and, more recently, neuropsychiatric disorders [15,16,17]. Several of these diseases are associated with changes in the hippocampus and despite high expression of VGF in this brain region [18,19], the role of this neuropeptide in the hippocampus is not fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…As yet there is no information on the VGF receptors which could mediate the action of these peptides into the bloodstream, and further peptidomic investigations are warranted. Moreover, since reduction in the NERP-1 content is found in the frontal cortex of Alzheimer patients (Cocco et al, 2010) where ADH is found to be reduced (Labudova et al, 1998), together with its decrease in the hypothalamus (Mann et al, 1985), possible future studies may regard the involvement of NERPs in ADH mechanisms in these patients.…”
Section: Discussionmentioning
confidence: 97%
“…The rat VGF C-terminus, TLQP, rat PGH and NERP-1 antisera were produced as previously reported (Cocco et al, 2010) while in order to obtain NERP-2 antiserum, the rat VGF 342-350-NH2 peptide conjugated with bovine thyroglobulin via an additional D-tyrosine was used for guinea pig immunizations.…”
Section: Vgf Peptide Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation